Digital Divide in English Language Learning: Challenges in Remote Indonesian Islands - Mohlomi Molapo; Ava Brown; Tikitai Tewake (International Journal of Language and Ubiquitous Learning, 2025)
Background. The digital divide remains a persistent challenge within Indonesia’s education system, particularly in remote island regions where access to technology and reliable internet infrastructure is limited Purpose. This study aimed to investigate the barriers and implications of the digital divide in English language learning among students in Indonesia’s remote islands. It focused on three key dimensions: access to digital infrastructure, teacher readiness for technology-mediated instruction, and students’ digital literacy. Method. A mixed-method research design was employed involving 150 English teachers and 300 students from ten remote islands in eastern Indonesia. Quantitative data were collected through structured questionnaires, while qualitative data were obtained from in-depth interviews and classroom observations. Results. The findings revealed that inadequate internet connectivity, limited availability of digital devices, and insufficient teacher training significantly hinder effective English language instruction. Statistical analysis showed that students in underconnected regions scored approximately 35% lower on digital-based English learning assessments compared to their urban counterparts. Conclusion. The study concludes that the digital divide not only restricts progress in English language learning but also intensifies educational inequality and social exclusion in remote regions of Indonesia.